Role of H2O2-activated TRPM2 calcium channel in oxidant-induced endothelial injury - Hecquet, Claudie M.; Malik, Asrar B. (Thrombosis and Haemostasis, 2009)
The transient receptor potential (melastatin) 2 (TRPM2), is an oxidant-activated non-selective cation channel that is widely expressed in mammalian tissues including the vascular endothelium. Oxidative stress, through the generation of oxygen meta-bolites including H2O2, stimulates intracellular ADP-ribose formation which, in turn, opens TRPM2 channels. These channels act as an endogenous redox sensor for mediating oxidative stress/ROS-induced Ca2+ entry and the subsequent specific Ca2+-dependent cellular reactions such as endothelial hyper-permeability and apoptosis. This review summarizes recent findings on the mechanism by which oxidants induce TRPM2 activation, the role of these channels in the signalling vascular endothelial dysfunctions, and the modulation of oxidant-induced TRPM2 activation by PKCα and phospho-tyrosine phosphates L1.
Keywords: TRPM2; oxidative stress; endothelial cells